Viroid-like sequences of coconut: Proceedings of a meeting, 21 April 1997, Kajang (Kuala Lumpur), Malaysia - Diekmann, M. (1997)
Recognizing the necessity of resolving the issue of viroid-like sequences in coconuts, ACIAR, IPGRI and COGENT organized the workshop at which participants from laboratories in Australia, France, Italy and the Philippines presented summaries of their research and discussed the quarantine relevance of the viroid-like sequences in coconuts. The meeting participants formulated a research agenda to close apparent research gaps. The result of the workshop, including the recommendations for the treatment of coconut viroids and viroid-like sequences, are presented in this report. It is hoped that implementation of these recommendations will open the way for essential exchange and movement of coconut germplasm, while at the same time preventing the spread of pathogens.